Rising trends in obesity prevalence among Royal Thai Army personnel from 2017 to 2021 - Boonsub Sakboonyarat; Jaturon Poovieng; Kanlaya Jongcherdchootrakul; Phutsapong Srisawat; Panadda Hatthachote; Mathirut Mungthin; Ram Rangsin (Scientific Reports, 2022)
Abstract Obesity is an essential health issue leading to noncommunicable diseases (NCDs) as well as atherosclerotic cardiovascular diseases. We aimed to determine the trends in obesity prevalence among Royal Thai Army (RTA) personnel and their associated factors using the health examination of RTA personnel database. A series of cross-sectional studies were conducted from 2017 to 2021. A self-report guide was created using a standardized case report form to obtain demographic characteristics and determine behavioral risk factors. Obesity was defined as BMI $$\ge$$ ≥ 25 kg/m2, and a total of 512,476 RTA personnel nationwide were included. Obesity prevalence rose from 42.1% (95% CI 41.7–42.4) in 2017 to 44.2% (95% CI 43.9–44.5) in 2021 (p for trend < 0.001). A significant surge was observed in obesity prevalence among young RTA personnel aged 18–24 years from 23.7% in 2017 to 28.4% in 2021 (p for trend < 0.001). Higher age individuals, male participants and RTA personnel residing in Bangkok tended to have a significantly higher risk for obesity. Further, regular exercise was a protective factor for obesity. Our data emphasized that obesity among the RTA personnel has been continuously rising over one half-decade, especially among young adults.